Review on sulfide stress cracking in sour service for OCTG and recent advances in modeling of hydrogen-assisted fracture - Elkhodbia, Mohamed; Negi, Alok; Mubarak, Ghadeer; Barsoum, Imad; AlFantazi, Akram (Geoenergy Science and Engineering, 2023)
Sulfide stress cracking (SSC) presents a complex hydrogen-assisted cracking problem in oil and gas (O&G) production, primarily due to the presence of a wet hydrogen sulfide (H2S) environment. Recognized as a form of hydrogen embrittlement, SSC profoundly impacts the performance and durability of oil country tubular goods (OCTG), with potential adverse financial and environmental consequences. For instance, casings play a crucial role as mechanical barriers throughout drilling, completion, and production operations. However, their exposure to sour service conditions renders them susceptible to SSC and premature failures. The O&G industry currently faces multiple challenges in material selection and designing for sour service conditions to effectively mitigate SSC-related failures. This article aims to provide an in-depth review encompassing design practices, material qualification standards, and experimental testing methodologies used to assess the susceptibility of OCTG to SSC under sour service conditions. This work also examines recent advancements in fracture mechanics-based modeling approaches, which offer accurate simulation capabilities for hydrogen-assisted failures of practical engineering significance.